2006
DOI: 10.1093/carcin/bgi356
|View full text |Cite
|
Sign up to set email alerts
|

Specific TP53 mutation pattern in radiation-induced sarcomas

Abstract: The mutagenic properties of ionizing radiation are well known, but the presence of specific mutations in human radiation-induced tumours is not established. We have studied a series of 36 secondary sarcomas arising in the irradiation field of a primary tumour following radiotherapy. The allelic status and the presence of mutations of the TP53 gene were investigated. The mutation pattern was compared with data from sporadic sarcomas recorded in the IARC TP53 somatic mutations database. A high proportion (58%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 43 publications
2
50
0
Order By: Relevance
“…We recently analysed the presence of TP53 mutations in a series of sarcomas developing in the irradiation field in patients treated by radiotherapy. One-third of these patients have been treated for a bilateral retinoblastoma (Gonin-Laurent et al, 2006). In this series of sarcomas, the rate of TP53 mutations was high (58%), and the mutation spectrum was characteristic of radiation exposure.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…We recently analysed the presence of TP53 mutations in a series of sarcomas developing in the irradiation field in patients treated by radiotherapy. One-third of these patients have been treated for a bilateral retinoblastoma (Gonin-Laurent et al, 2006). In this series of sarcomas, the rate of TP53 mutations was high (58%), and the mutation spectrum was characteristic of radiation exposure.…”
Section: Introductionmentioning
confidence: 76%
“…Thirty-six sarcomas developing in the field of irradiation of a primary cancer were collected at the Institut Curie (Table 1 and (Gonin-Laurent et al, 2006). Twelve of these sarcomas developed in patients treated for bilateral retinoblastoma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] It has also been shown that both the RB1 and p52 genes are commonly mutated in radiation-induced sarcomas, suggesting that loss of these tumor-suppressor genes plays a role in the development of these lesions. 17,18 Friend et al proposed a link between retinoblastomas and osteosarcomas. 19 Two patients in our series had retinoblastoma as the original lesion, for which they received radiation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While some exposures are thought to leave very specific somatic mutations in such genes as p53 (Jones et al, 1991;Gonin-Laurent et al, 2006), most cancers and other chronic diseases do not reveal their causes through any such specific ''fingerprints. '' Although Hunter (2005) suggested that ''the finding of an interaction between exposure to a complex mixture and a specific variant of a metabolic gene ''points the finger'' at the substrates of the gene as the causal components of the complex mixture'' and the germ of this idea can also be found elsewhere (Ames, 1999;Potter, 2001;Rothman et al, 2001;Brennan, 2002), these ideas appear not to have been developed in any formal statistical framework.…”
Section: Introductionmentioning
confidence: 99%